2016
DOI: 10.1136/injuryprev-2015-041750
|View full text |Cite
|
Sign up to set email alerts
|

Fatal river drowning: the identification of research gaps through a systematic literature review

Abstract: IntroductionDrowning is a leading cause of unintentional death. Rivers are a common location for drowning. Unlike other location-specific prevention efforts (home swimming pools and beaches), little is known about prevention targeting river drowning deaths.MethodsA systematic literature review was undertaken using English language papers published between 1980 and 2014, exploring gaps in the literature, with a focus on epidemiology, risk factors and prevention strategies for river drowning.ResultsTwenty-nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 48 publications
3
58
0
3
Order By: Relevance
“…While there were some judgmental comments on the risky behavior of the youthful divers, older swimmers, 'who should know better' were also identified as disregarding their own, and at times, others safety. Given known associations between rivers and suicide (Peden et al, 2016), the breaking of the water referred to by Sherr (2012) may equally see broken water closing behind people in more definitive ways.…”
Section: Discussion: Health From Sedimented Swimming Encountersmentioning
confidence: 99%
“…While there were some judgmental comments on the risky behavior of the youthful divers, older swimmers, 'who should know better' were also identified as disregarding their own, and at times, others safety. Given known associations between rivers and suicide (Peden et al, 2016), the breaking of the water referred to by Sherr (2012) may equally see broken water closing behind people in more definitive ways.…”
Section: Discussion: Health From Sedimented Swimming Encountersmentioning
confidence: 99%
“…A recent study also suggested that drowning prevention interventions based on site-specific locations are likely to have a greater impact than general strategies aimed at preventing drowning 7. This is the first study, to the best of our knowledge, to calculate the drowning mortality rate using aquatic area as the denominator.…”
Section: Discussionmentioning
confidence: 93%
“…Calculation of the drowning rate using population as the denominator will underestimate the risk of drowning, as it includes many people who are never or very rarely exposed to water and consequently, to the risk of drowning 9. In a systematic review of fatal river drowning studies, Peden et al 7 suggested that population-based rates do not take exposure into account and recommended that future studies should aim to identify exposure at river locations to calculate a more accurate drowning rate. To better identify regions with a higher risk of drowning deaths, we sought in this study to compare the rankings of regional drowning mortality rates according to population-based versus aquatic area-based rates in Taitung County, Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Further work is required to improve rivers and rescue knowledge, areas in which our understanding has improved over the last few years (Franklin & Pearn, 2011;Pearn & Franklin, 2012;Peden, Franklin, & Leggat, 2016a). Overall, females demonstrated higher levels of knowledge on all categories when compared to males.…”
Section: Discussionmentioning
confidence: 99%